Evaluation of Physic-chemical Parameters of Water Quality on Agricultural Fields of Western Bahia - do Rego, Enoc Lima; Gomes, Daniel Batista; da Silva Junior, Jorge; Herok, Diego Lucena; Porto, Eneas Denieste de Oliveira; Leite, Oldair Donizeti (Orbital: The Electronic Journal of Chemistry, 2017)
For the diagnosis of the quality of water it is necessary to execute a set of analyzes (physical and chemical) of the body of water that will provide information that integrate biotic and abiotic factors that govern the functioning of the ecosystem. The objective of this study is to evaluate the quality of water from wells and rivers of Urucuia aquifer region for investigation of contamination or contamination risks. Were realize collections in nine (9) areas of western Bahia, which were collect in each area, two points of well water samples and a river, and determining the electrical conductivity, pH, dissolved ions and metals. The results were compare with the maximum permissible values (MPV) for human consumption by Ordinance No. 2914/11 of the Ministry of Health and National Environment Counsel - CONAMA (Resolution 357 and supplementary resolutions). The quantitative results of the analysis showed that the surface and well waters that are part of the aquifer Urucuia within the parameters investigated are below the values recommended by the legislation showing that the agricultural activities in the region has not affected to the evaluated parameters, the quality of water for human consumption. However, it is necessary a monitoring of surface and groundwater in the region with expansion parameters evaluated. DOI: http://dx.doi.org/10.17807/orbital.v9i2.880